The effect of intravitreal bevacizumab on ocular blood flow in diabetic retinopathy and branch retinal vein occlusion as measured by laser speckle flowgraphy - Nitta F (Dove Medical Press, 2014)
Fumihiko Nitta,1 Hiroshi Kunikata,1,2 Naoko Aizawa,1 Kazuko Omodaka,1 Yukihiro Shiga,1 Masayuki Yasuda,1 Toru Nakazawa1–31Department of Ophthalmology, Tohoku University Graduate School of Medicine, Sendai, Japan; 2Department of Retinal Disease Control, Tohoku University Graduate School of Medicine, Sendai, Japan; 3Department of Advanced Ophthalmic Medicine, Tohoku University Graduate School of Medicine, Sendai, JapanBackground: This study evaluated the effect of intravitreal injection of bevacizumab (IVB) on macular edema associated with diabetic retinopathy (DME) or branch retinal vein occlusion (BRVOME) using laser speckle flowgraphy.Methods: A comparative interventional study of 25 eyes from 22 patients with macular edema (DME group: 12 eyes; BRVOME group: 13 eyes) who underwent IVB. Mean blur rate (MBR) was measured in the retinal artery, retinal vein, optic nerve head (ONH), and choroid before and after IVB. Results: In the BRVOME group, there was no significant change in MBR in the retinal artery, retinal vein or ONH, but choroidal MBR decreased significantly (P=0.04). In the DME group, the MBR in the retinal artery, retinal vein, ONH, and choroid decreased significantly (P=0.02, P=0.04, P<0.001, and P=0.04, respectively). In the DME group, pre-IVB MBR in the ONH was significantly correlated with post-IVB foveal thickness (R= -0.71, P=0.002). There was no such correlation in the BRVOME group in the ONH.Conclusion: IVB had a suppressive effect on circulation in eyes with DME but not in those with BRVOME. This suggests that this noninvasive and objective biomarker may be a useful part of pre-IVB evaluations and decision-making in DME.Keywords: macular edema, mean blur rate, optic nerve head, biomarker, ocular circulation